Health Promotion Program (JUMSIH); To Enhance Children's Clean and Healthy Living Knowledge - Yufiarti, Yufiarti; Edwita; Suharti (Program Studi Magister Pendidikan Anak Usia Dini, 2019)
Knowledge about clean and healthy life in children needs to be given early to shape behavior in everyday life. Knowledge about healthy living can be provided at school through various learning programs. This study aims to find the effectiveness of health promotion programs (JUMSIH) to increase children's knowledge about clean and healthy living. The research method is a pre-experimental one-shot case study design. The respondents of this study were 68 students aged 7-8 years. The results showed that the JUMSIH program can help children have knowledge about healthy living. Based on data analysis, n = 15 generally obtained scores above 2.6. It was concluded that healthy living skills are often performed by students such as hand washing, bathing, and toothbrush behavior which are basic skills for children to be able to live healthy lives. Suggestions for further research which is the development of various programs to increase awareness of clean and healthy living from an early age. Keywords: Clean and healthy life Knowledge, Early Childhood, Health Promotion Program (JUMSIH) References: Akçay, N. O. (2016). Implementation of Cooperative Learning Model in Preschool. Journal of Education and Learning, 5(3), 83–93. https://doi.org/10.5539/jel.v5n3p83 Allport, B. S., Johnson, S., Aqil, A., Labrique, A. B., Nelson, T., KC, A., … Marcell, A. V. (2018). Promoting Father Involvement for Child and Family Health. Academic Pediatrics, 18(7), 746–753. https://doi.org/10.1016/j.acap.2018.03.011 Bonuck, K. A., Schwartz, B., & Schechter, C. (2016). Sleep health literacy in head start families and staff: Exploratory study of knowledge, motivation, and competencies to promote healthy sleep. Sleep Health, 2(1), 19–24. https://doi.org/10.1016/j.sleh.2015.12.002 Considerations, P., & Framework, N. Q. (2010). Health , Hygiene and Infection Control Strategies for Policy Implementation :2010(Vic). Conti, G., Heckman, J. J., & Pinto, R. (2016). The Effects of Two Influential Early Childhood Interventions on Health and Healthy Behaviour. Economic Journal, 126(596), F28–F65. https://doi.org/10.1111/ecoj.12420 Creswell, J. W. (2012). Educational Research Planning, Conducting, and Evaluating Quantitative and Qualitative Research(4th ed.; P. A. Smith, Ed.). Boston: Pearson. Duxbury, T., Bradshaw, K., Khamanga, S., Tandlich, R., & Srinivas, S. (2019). Environmental health promotion at a National Science Festival: An experiential-education based approach. Applied Environmental Education and Communication, 0(0), 1–16. https://doi.org/10.1080/1533015X.2019.1567406 Fernandez-Jimenez, R., Al-Kazaz, M., Jaslow, R., Carvajal, I., & Fuster, V. (2018). Children Present a Window of Opportunity for Promoting Health: JACC Review Topic of the Week. Journal of the American College of Cardiology, 72(25), 3310–3319. https://doi.org/10.1016/j.jacc.2018.10.031 Fung, C., Kuhle, S., Lu, C., et al. (2012). From “best practice” to “next practice”: the effectiveness of school-based health promotion in improving healthy eating and physical activity and preventing childhood obesity. Int. J. Behav. Nutr. Phys. Act., 9, 27. Gall, M. D., Gall, J. P., & Borg, W. R. (2007). Educational Research: An Introduction (4th ed.). New York: Longman Inc. Goldfeld, S., O’Connor, E., O’Connor, M., Sayers, M., Moore, T., Kvalsvig, A., & Brinkman, S. (2016). The role of preschool in promoting children’s healthy development: Evidence from an Australian population cohort. Early Childhood Research Quarterly, 35, 40–48. https://doi.org/10.1016/j.ecresq.2015.11.001 Hawe, P., Potvin, L. (2009). What is population health intervention research. Can. J. Public Health, 100 (Suppl I8–14). Julianti, R., Nasirun, M., & Wembrayarli. (2018). Pelaksanaan Perilaku Hidup Bersih dan Sehat (PHBS) di Lingkungan Sekolah. Jurnal Ilmiah Potensia, 3(1), 11–17. Kasnodihardjo, K. (2010). Metode pelembagaan perilaku hidup sehat kaitannya dengan kesehatan lingkungan dan hygiene perorangan pada keluarga di Subang Jabar. Keshavarz, N., Nutbeam, D., Rowling, L., Khavarpour, F. (2010). Schools as social complex adaptive systems: a new way to understand the challenges of introducing the health promoting schools concept. Soc. Sci. Med., (70), 1467–1474. Kobel, S., Wartha, O., Wirt, T., Dreyhaupt, J., Lämmle, C., Friedemann, E. M., … Steinacker, J. M. (2017). Design, implementation, and study protocol of a kindergarten-based health promotion intervention. BioMed Research International, 2017. https://doi.org/10.1155/2017/4347675 Langford, R., Bonell, C.P., Jones, H. E. (2014). The WHO health promoting school framework for improving the health and well-being of students and their academic achievement. Cochrane Database Syst, Rev. 4, CD008958. Manning, M. L., & Lucking, R. (1991). The what, why, and how of cooperative learning. The Clearing House. 64(3), 152–156. Marlina, R. L. (2011). Analisis Manajemen Promosi Kesehatan Dalam Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) Tatanan Rumah Tangga di Kota Padang Tahun 2011. Padang: Universitas Andalas. Maryunani, A. (2013). Perilaku Hidup Bersih dan Sehat. Jakarta: Trans Info Media. McClure, M., Tarr, P., Thompson, C. M., & Eckhoff, A. (2017). Defining quality in visual art education for young children: Building on the position statement of the early childhood art educators. Arts Education Policy Review, 118(3), 154–163. https://doi.org/10.1080/10632913.2016.1245167 Mcisaac, J. D., Sim, S. M., Penney, T. L., & Kirk, S. F. L. (2012). School Health Promotion Policy in Nova Scotia: A Case Study. Revue PhénEPS / PHEnex Journal, 4(2). McIsaac, J. L. D., Penney, T. L., Ata, N., Munro-Sigfridson, L., Cunningham, J., Veugelers, P. J., … Kuhle, S. (2017). Evaluation of a health promoting schools program in a school board in Nova Scotia, Canada. Preventive Medicine Reports, 5, 279–284. https://doi.org/10.1016/j.pmedr.2017.01.008 Midcentraldhb. (2014). Health and Safety Guidelines for Early Childhood Education Services. https://doi.org/2014 Mikkonen, J., Raphael, D. (2010). Social Determinants of Health: The Canadian Facts. University School of Health Policy and Management Toronto. Proverawati, A. (2012). Perilaku Hidup Bersih dan Sehat. Yogyakarta: Nuha Medika. Reed, K.E., Warburton, D.E., Macdonald, H.M., Naylor, P.J., McKay, H. A. (2008). Action Schools! BC: a school-based physical activity intervention designed to decrease cardiovascular disease risk factors in children. Prev. Med, 46, 525–531. Samdal, O., Rowling, L. (2011). Theoretical and empirical base for implementation components of health-promoting schools. Health Educ., 111, 367–390. Syukriyah, E. (2011). Gambaran Pengetahuan, Sikap dan Tindakan Murid SD Tentang PHBS di SDN 06 Lubuk LayangPadang. Padang: Poletkkes Kemenkes Padang. Veugelers, P. J., & Schwartz, M. E. (2010). Comprehensive school health in Canada. Canadian Journal of Public Health = Revue Canadienne de Sante Publique, 101 Suppl(August), S5-8. https://doi.org/10.17269/cjph.101.1907 WHO. (2016). What is a health promoting school? WIjayanti, N. A. (2017). Implementation of Role Playing Method in the Hygiene Hadith Learning Toward Early CHildrens Healthy Behavior of Group B in Dabin Aggrek Gunungpati Semarang. Early Childhood Education Papers (Belia), 6(2).